Observations and modeling of the braking effect of forests on small and medium avalanches - Feistl, Thomas; Bebi, Peter; Teich, Michaela; Bühler, Yves; Christen, Marc; Thuro, Kurosch; Bartelt, Perry (Journal of Glaciology, 2014)
ISSN:0022-1430 ISSN:1727-5652